2003
DOI: 10.1097/01.sla.0000090447.73384.ad
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Assist Devices as Permanent Heart Failure Therapy

Abstract: The cost of long-term LVAD implantation is commensurate with other life-saving organ transplantation procedures like liver transplantation. As an evolving technology, there are a number of opportunities for improvement that will likely reduce costs in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 14 publications
0
72
0
1
Order By: Relevance
“…However, the principal limitations of VADs as long-term treatment approaches for heart failure are those affecting any non-endothelialized foreign body: (1) infection, and (2) thromboembolic and bleeding complications (Oz et al, 2003). These data are well documented in a prospective, randomized clinical trial (REMATCH Rose et al, 2001).…”
Section: Ventricular Thrombosismentioning
confidence: 71%
“…However, the principal limitations of VADs as long-term treatment approaches for heart failure are those affecting any non-endothelialized foreign body: (1) infection, and (2) thromboembolic and bleeding complications (Oz et al, 2003). These data are well documented in a prospective, randomized clinical trial (REMATCH Rose et al, 2001).…”
Section: Ventricular Thrombosismentioning
confidence: 71%
“…However, other CE studies confirmed that the main cost drivers in this population are the devices, the procedure and the post‐procedure complications costs 26. In the Oslo University experience, medical therapy represented 1% of total costs during the pre‐LVAD and the LVAD phase and was insignificant during the post‐LVAD phase 10.…”
Section: Discussionmentioning
confidence: 85%
“…Infections in these patients also incur a higher economic burden as these patients tend to have longer recovery time and require more hospitalizations [5]. Cost analysis also shows that sepsis is the most important predictor of cost [6]. Antimicrobial topical wound care for CF-LVADs is a simple intervention that is now routine despite the paucity of research on its efficacy.…”
Section: Discussionmentioning
confidence: 99%